2022
DOI: 10.1007/s12144-021-02672-w
|View full text |Cite
|
Sign up to set email alerts
|

Construction and evaluation of a mindfulness-based quality of life and well-being program (MQW) in a randomized trial

Abstract: Due to the multi-factorial nature of the self-report of happiness, an enhancement program was designed that focused on mental style (subjective processes), and relationships, work, money, health, and leisure (objective life domains). An examination of interventions revealed mindfulness training (subjective factors) and goal setting (objective factors) as effective change modalities. To address this, the Mindfulness-based Quality of Life and Well-being Program (MQW) was developed and evaluated against the Mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 151 publications
2
5
0
Order By: Relevance
“…As the present study drawn results indicated, the educational intervention has led to an increase in the mean psychological well-being of the experimental group compared to the control group, implying the effectiveness of training in promoting the psychological well-being of the experimental group. This finding was consistent with the results of various studies, such as the ones conducted by Ajilchi et al (2022) [ 25 ], Jones et al (2022) [ 26 ], Zheng et al (2022) [ 27 ], Monemiyan et al (2021) [ 28 ]. In many cases, of female heads of households are not aware of the appropriate behavior in times of hardship and show an inappropriate reaction to it unintentionally, but with training based on mindfulness, women can improve their knowledge of how to deal with hardship.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the present study drawn results indicated, the educational intervention has led to an increase in the mean psychological well-being of the experimental group compared to the control group, implying the effectiveness of training in promoting the psychological well-being of the experimental group. This finding was consistent with the results of various studies, such as the ones conducted by Ajilchi et al (2022) [ 25 ], Jones et al (2022) [ 26 ], Zheng et al (2022) [ 27 ], Monemiyan et al (2021) [ 28 ]. In many cases, of female heads of households are not aware of the appropriate behavior in times of hardship and show an inappropriate reaction to it unintentionally, but with training based on mindfulness, women can improve their knowledge of how to deal with hardship.…”
Section: Discussionsupporting
confidence: 92%
“…In study done by Ajilchi et al (2022) with the goal to find out the efffect of mindfulness-based training program on mental toughness and psychological well-being of female athletes, the result showed that mindfulness-based training program can be useful for psychological well-being [ 25 ]. Moreover, in the studies performed by Jones et al (2022) [ 26 ] and Zheng et al (2022) [ 27 ], the results were identical. These researchers reported that mindfulness-based intervention can improve psychological well-being and the quality of life [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 58%
“…Another departure is the meta-theoretical assumption, in Buddhist mindfulness theory, of the absence of a continuous self (Shonin, Van Gordon, Singh, & Griffiths, 2015), a construct that is wholly different from a robust sense of self and its perceived benefits (Guerrettaz & Arkin, 2016;Sheldon et al, 1997). There are, however, some examples of where the modern use of mindfulness extends its reach into some of the goals of traditional mindfulness (Lorenz, 2009), such as practices that teach, through observational or meta-awareness techniques, to non-judgmentally watch the fluctuating nature of the mind itself, which can lead to freedom from top down processes (Chiesa et al, 2013;Jones & Drummond, 2022;Siegel, 2007).…”
Section: Mindfulnessmentioning
confidence: 99%
“…Temporal stability along with sensitivity to change is critical for measures of well-being as they must be robust enough to withstand momentary fluctuations in mood states and yet reflect genuine changes in subjective experience [46]. As reliability estimates are used to evaluate the stability of measures administered at different times to the same individuals, in a follow up study the CLINQOL was evaluated for its test-retest reliability [47].…”
Section: Reliabilitymentioning
confidence: 99%